Emergent quasicrystal in fermionic superradiance - Bo-Hao Wu; Xin-Xin Yang; Wei Zhang; Yu Chen (Physical Review Research)
Quasicrystal is state of matter with multiple crystalline orders, displaying a short-range density-wave order and a long-range disorder. As an exotic state lying in between crystals and Anderson insulators, its dynamical formation is little discussed. Here, we study the emergence of quasicrystalline order in fermionic superradiance, where Fermi statistics plays a crucial role, being distinct from its bosonic counterpart where interaction is the stabilizer. Owing to quasicrystalline orders, there exist multiple energy gaps opening at different quasicrystalline order strength, which can modify the density of states in excitation spectrum. As a result, the effective ground-state energy is strongly modified and the superradiant quasicrystal transition becomes first order and density dependent. This new mechanism leads to a linear V-shape kink of the fermionic superradiance transition line near a filling which uniquely relates to the quasicrystalline order. Our findings demonstrate that quasicrystal can be realized in fermionic superradiance as a result of Fermi statistics and be verified by characteristic density-dependent phenomena.